Challenges and advances in the use of cannabidiol in the treatment of patients with refractory epilepsy: An integrative review (Research, Society and Development, 2023)
Introduction: Epilepsy is a neurological syndrome characterized by two or more spontaneous epileptic seizures,     caused by excessive neuronal discharges due to different etiologies. Currently, there are numerous drugs available to control it. However, a portion of the population is drug resistant, that is, seizures occur even with appropriate use of antiepileptic drugs. Clinical trials since 1980 have demonstrated the anticonvulsant and neuroprotective properties of cannabidiol - the non-psychoactive component of Cannabis Sativa -. However, there is not a satisfactory amount of research that reliably establishes the adverse effects of CBD. Objectives: To add knowledge, through analysis of studies regarding the therapeutic management of cannabidiol in refractory epilepsy. Methodology: This is an integrative literature review. The research was carried out in July 2023, based on the PICO strategy. Using the descriptors “cannabidiol and refractory epilepsy”, “challenges of cannabidiol refractory epilepsy”, “cannabidiol and epilepsy”. As inclusion criteria, there are articles from the last ten years in any language. Results: 1,293 results were found in the PubMed, Virtual Health Library and Google Scholar databases. After the analysis and exclusion stages, 12 studies met the full text evaluation and eligibility criteria. Conclusion: Given these results, there is a need for studies that corroborate the efficacy and safety of cannabidiol in refractory epilepsy, in order to eliminate the limitations of the treatment and resolve the challenges in relation to its approval and use.